Nano porous systems for storing hydrogen-based clean fuel - Harsh Prashar (Open Journal of Chemistry - Peertechz Publications, 2021)
Rapid growth in population, Concerns about the industrial revolution, environmental and energy issues are growing, and are urging the use of clean, renewable energy sources to ameliorate the dire situation. Hydrogen is an ideal synthetic fuel because it is light, very broad, and is an oxidation product (water), i.e. environmentally friendly, but storage problems remain [1-3].